Experimental analysis of tensile properties and essential work of fracture of fumed silica filled polypropylene toughened with thermoplastic polyolefin elastomer. (July 2022) - Sadeghi, Alireza; Ashenai Ghasemi, Faramarz; Fasihi, Mohammad; Rajaee, Pouya
In this research, tensile and fracture behavior of polypropylene (PP) toughened with two types of thermoplastic polyolefin elastomers (TPOs) and filled with fumed silica are investigated. The TPOs are both propylene- and ethylene-based thermoplastic elastomers. Three percentages of TPO (0, 10, and 20 wt%) and four percentages of fumed silica (0, 1, 3, and 5 wt.%) are used. The addition of ethylene-based TPO to PP show higher values of modulus and tensile strength than propylene-based TPO. In contrast, propylene-based TPO show higher elongation at break which by increasing this type of TPO the elongation at break increase by 788%. The presence of fumed silica in the PP/TPOs blend improve the tensile strength and modulus but declined the elongation at break. Fracture behavior analysis of these compounds is performed by utilizing the essential work of fracture (EWF) approach. The outcomes demonstrate that both types of TPO in PP cause cavitation and fibrillar structures that increased the elastic and plastic work of fracture. Adding 10 wt.% ethylene- and propylene-based TPO to PP, the values of w e and βw p increase by 63%, 100% and 124%, 123%, respectively. Morphological observations show that fumed silica is located mainly around TPOs particles or at the PP/TPOs interfaces. The addition of fumed silica also reduce the size of the pores, which indicate a slight reduction in the amount of plastic work. However, fumed silica with low percentages increase the amount of elastic work and then reduce it. Also, the compound with 10 wt.% propylene-based thermoplastic elastomers and 1 wt.% fumed silica had the best toughness-stiffness-strength balance among the samples based on the optimization results.